A retrospective cross-sectional study of type 2 diabetes overtreatment in patients admitted to the geriatric ward - Wojszel, Zyta Beata (BMC Geriatr, 2019)
BACKGROUND: Glycemic control targets in older patients should be individualized according to functional status and comorbidities. The aim of the study was to identify high-risk patients who had evidence of tight glycemic control and thus at risk of serious hypoglycemia. METHODS: Retrospective cross-sectional study of type 2 diabetes patients admitted to the geriatric ward receiving diabetes medications. Patients’ hospital records were analyzed. The high risk of hypoglycemia group constituted patients who were aged 80+ years, diagnosed with dementia, with end- stage renal disease, or with a history of macrovascular complications. The primary outcome measure was hemoglobin A(1C) (HbA(1C)) ≤ 7.0% [53 mmol/mol]. RESULTS: Two hundred thirteen patients were included (77.5% women; 49.3% 80+ year-old). 65.3% received sulfonylurea, 39,4%- metformin, 32.9%- insulin, and 4.2%- acarbose (in 61.5% as monotherapy, and in 38.5% combination therapy). We identified 130 patients (60%) as the denominator for the primary outcome measure; 73.1% had a HbA(1C) value ≤7.0% [53.3 mmol/mol], but 55.4% ≤6,5% [48.8 mmol/mol], and 40.8% ≤6.0% [42 mmol/mol]. CONCLUSIONS: The results show a very high rate of tight glycemic control in older patients admitted to the geriatric ward, for whom higher HbA(1C) targets are recommended. This indicates the high probability of diabetes overtreatment in this group, associated with a high risk of recurrent hypoglycemia. This is all the more likely because most of them received medications known to cause hypoglycemia. This points to the need of paying more attention to specific difficulties in diabetes treatment in older people, especially those suffering from various geriatric syndromes and diseases worsening their prognosis.